The left axillary artery is a reasonable option as the inflow site for saphenous vein graft in minimally invasive coronary artery bypass grafting - Ushioda, Ryohei; Hirofuji, Aina; Yoongtong, Dit; Sakboon, Boonsap; Cheewinmethasiri, Jaroen; Lokeskrawee, Thanin; Patumanond, Jayanton; Lawanaskol, Suppachai; Kamiya, Hiroyuki; Arayawudhikul, Nuttapon (Frontiers in Cardiovascular Medicine, 2024)
This study aims to clarify the good inflow site for saphenous vein grafts (SVG) in minimally invasive off-pump coronary artery bypass grafting (mini-CABG), between the ascending aorta, the internal thoracic arteries (ITAs) and the left axillary artery (LAA). Methods This retrospective study included 126 patients who underwent Mini-CABG at our center between January 2014 and July 2023. Patients were divided into three groups according to the SVG inflow site for patency comparison: Aorta group (n=56), LAA group (n=23), and ITA group (n=47).There were 84 males, with mean age of 65.9 ± 7.0 years. There were no significant differences in preoperative characteristics between groups. Mean operation times were 254.6 ± 72.2, 213.7 ± 57.6, and 253.0 ± 81.2 min, and the average numbers of distal anastomoses were 2.9 ± 0.9, 2.4 ± 0.7 and 2.9 ± 1.1 in the Aorta, ITA and LAA groups respectively. Days in intensive care, hospital stay, and major complications did not differ between the groups. Early patency of SVG did not significantly differ among groups: 93.0% in the Aorta group, 98.0% in the ITA group, and 100% in the LAA group. Mean follow-up period was 136.7±295.7 days, and follow-up coronary CTA revealed 18 SVG occlusions (Aorta group n=8, ITA group n=5, LAA group n=5). The Kaplan-Meier curve for SVG patency rates did not show any significant differences among the three groups.The ascending aorta, the ITAs, and the LAA serve as reliable inflow sites with similar results in mini-CABG.